How Much Protoporphyrin IX Must Be Activated to Obtain Full Efficacy of Methyl Aminolevulinate Photodynamic Therapy? Implication for Treatment Modifications - Wulf, Hans Christian (Pharmaceuticals (Basel), 2021)
Photodynamic therapy (PDT) with methyl aminolevulinate (MAL) is a popular treatment for actinic keratoses (AK), and several PDT treatment modalities with similar cure rates are in use. The effect relies on the activation of protoporphyrin IX (PpIX) in premalignant cells. This study aimed to measure PpIX during each treatment modality to determine the minimal PpIX activation and shortest exposure time for optimal cure rate. In four different treatment modalities, we established the PpIX formation up to three hours after MAL application without illumination and measured the speed of PpIX photoactivation during 9 min of red light (37 J/cm(2)). The level of PpIX three hours after MAL application was set to 100 PpIX units. In comparison, 85 PpIX units were formed during daylight PDT, 57 PpIX units during pulse PDT, and 52 PpIX units without any curettage prior to MAL. The activation of 50 PpIX units should, therefore, be enough to obtain a full effect on AK. Further, red light illumination may be shortened from 9 min to 1–2 min. The results indicate that PDT can be performed successfully with half the illumination time used in daylight PDT today and with one fourth of the illumination time used in classical PDT.